CYTOPATHOLOGIC DIAGNOSIS OF LIVER MASS LESION - SARITA PARIHAR; SHARDA DAWAN; RAJESH KUMAR; MAMTA GARG (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study is to categorize and establish the various cytological patterns of liver lesions. Methods: The present study was a hospital-based both retrospective and prospective study, on 504 patients with liver space-occupying lesions (SOLs) as USG/CT-guided fine needle aspiration cytology or biopsy was done and the smears or tissue was sent to the Department of Pathology, for 5 years between January 2018 and December 2022. Investigations done before the procedure was platelet count and plasma prothrombin time to know patients with bleeding tendencies. Under ultrasonography guidance, fine needle aspiration was performed on patients diagnosed for nodular or diffuse lesions of the liver. Results: Mean age of the study population was 58.53±12.62 years, 60.32% were male, 87.30% were Hindu, and 68.45% were rural. The most common complaint was pain abdomen 384 (76.19%) followed by jaundice 70 (13.89%). About 95.44% were neoplastic nature out of which 98.96% were malignant, out of which 83.61% were secondary. Out of 64 primary neoplastic lesions, maximum 98.44% were hepatocellular carcinoma. Out of 398 secondary neoplastic lesions, maximum 87.69% were metastatic carcinoma. Conclusion: We concluded that in any SOL, the screening of the liver is essential for early detection and long survival of cases.